Advancements in melanoma cancer metastasis models. (7th February 2023) - Nascentes Melo, Luiza Martins; Kumar, Suresh; Riess, Valeria; Szylo, Krystina J.; Eisenburger, Robin; Schadendorf, Dirk; Ubellacker, Jessalyn M.; Tasdogan, Alpaslan
Abstract: Metastatic melanoma is a complex and deadly disease. Due to its complexity, the development of novel therapeutic strategies to inhibit metastatic melanoma remains an outstanding challenge. Our ability to study metastasis is advanced with the development of in vitro and in vivo models that better mimic the different steps of the metastatic cascade beginning from primary tumor initiation to final metastatic seeding. In this review, we provide a comprehensive summary of in vitro models, in vivo models, and in silico platforms to study the individual steps of melanoma metastasis. Furthermore, we highlight the advantages and limitations of each model and discuss the challenges of how to improve current models to enhance translation for melanoma cancer patients and future therapies.